2010
DOI: 10.3846/jcem.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

The Quasi-Ductile Resistance of Compressed Spun Concrete Beam‐columns

Abstract: Abstract. The expediency of reinforcing precast spun concrete members of annular cross sections reinforced by highstrength steel bars is discussed. Test materials, mechanical properties, production and testing procedures of plain and reinforced spun concrete specimens are presented. The quasi-ductile strength and strain features of concentrically and eccentrically loaded specimens are considered. The modelling of a bearing capacity of beam-columns of annular cross sections is based on the concepts of bending w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The circular concrete-filled steel tubular (CFST) columns are characteristic of ductility, strength and a wide range of possibilities enabling incorporation of advanced materials and techniques, like spun concrete, thus making them the go-to solution when the traditional design fails. Centrifugal casting enables decreasing porosity of the concrete, increasing its homogeneity and strength, while minimizing self-weight by forming an annular cross section (Kliukas, Kudzys, & Vadlūga, 2010). The study has shown (Kvedaras & Sapalas, 1999) that, in case of a conventional multistorey building, in a non-seismic area, a mixed framework with hollow core CFST columns could reduce usage of steel and concrete by half in comparison to a regular reinforced concrete frame.…”
Section: Introductionmentioning
confidence: 93%
“…The circular concrete-filled steel tubular (CFST) columns are characteristic of ductility, strength and a wide range of possibilities enabling incorporation of advanced materials and techniques, like spun concrete, thus making them the go-to solution when the traditional design fails. Centrifugal casting enables decreasing porosity of the concrete, increasing its homogeneity and strength, while minimizing self-weight by forming an annular cross section (Kliukas, Kudzys, & Vadlūga, 2010). The study has shown (Kvedaras & Sapalas, 1999) that, in case of a conventional multistorey building, in a non-seismic area, a mixed framework with hollow core CFST columns could reduce usage of steel and concrete by half in comparison to a regular reinforced concrete frame.…”
Section: Introductionmentioning
confidence: 93%
“…The subject of shear forces associated with ductility was studied by Jensen and Lapko (2009). Kliukas et al (2010) reported a study on ring beam-columns under bending and compressive forces. They found that high strength reinforcement steel led to higher ductility when compared with normal strength reinforcement steel.…”
Section: Overview and Significance Of Researchmentioning
confidence: 99%
“…Input data is obtained from experimental research (e.g., Amšiejus et al 2009Amšiejus et al , 2010. In the case of steel-concrete structures, stability occurs mainly in concrete columns reinforced by high strength steel bars (Kliukas et al 2010) and composite columns (Guezouli et al 2010;Kala et al 2010). Characteristics of concrete and steel-concrete structures include long-term effects such as creep and shrinkage, which may cause loss of strength (Au, Si 2011).…”
Section: Stability and Reliability Of Structuresmentioning
confidence: 99%